Counseling Development (Aliza) in Pregnant Women - Yayu Humaeroh; Vivi Silawati; Triana Indrayani (Indonesian Journal of Global Health Research, 2025)
Anxiety in third-trimester pregnant women is a common psychological challenge faced before childbirth and has the potential to interfere with the delivery process. The general objective of this study was to identify and develop the ALIZA counseling model for third-trimester pregnant women. This study employed a mixed-method design with an exploratory sequential approach divided into three stages. Stage I was an exploratory qualitative study conducted through in-depth interviews with 10 third-trimester pregnant women, 5 midwives, 5 psychologists, and 5 counselors, selected purposively. Stage II involved the development of the counseling and the preparation of the ALIZA counseling guide. Stage III was a quantitative study to test the model's effectiveness using a pretest–posttest design with control and intervention groups, each consisting of 20 participants (total n=40). The instruments used were the DASS-21 anxiety scale questionnaire, and the analysis employed descriptive tests, normality tests, and the Wilcoxon test. Qualitative findings indicated that third-trimester pregnant women experienced anxiety due to lack of information, negative experiences, environmental pressure, and limited support from their partners. The counseling components formulated of Assessment, Listening, Information, Zone of Comfort, and Action Plan. Empathic and educational counseling, using psychological approaches such as affirmations and relaxation techniques, was shown to increase self-confidence and preparedness for childbirth. Quantitative results showed a decrease in mean anxiety scores from 19.22 to 16.45 in the intervention group, and the Wilcoxon test yielded a Z value of -5.560 with p = 0.000, indicating a statistically significant reduction in anxiety. Multivariate linear regression analysis showed that all ALIZA components had a significant effect on anxiety, with R² = 0.695, meaning that 69.5% of the variance in anxiety could be explained simultaneously by these five components.